2021
DOI: 10.1063/5.0040286
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven subgrid-scale modeling of forced Burgers turbulence using deep learning with generalization to higher Reynolds numbers via transfer learning

Abstract: Developing data-driven subgrid-scale (SGS) models for large eddy simulations (LES) has received substantial attention recently. Despite some success, particularly in a priori (offline) tests, challenges have been identified that include numerical instabilities in a posteriori (online) tests and generalization (i.e., extrapolation) of trained data-driven SGS models, for example to higher Reynolds numbers. Here, using the stochastically forced Burgers turbulence as the test-bed, we show that deep neural networks… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Retraining an ANN on such a data set might strike a useful balance between the robustness of online training and the economy of offline training. Similar approaches have shown promise for comparable problems (Subel et al., 2021); our preliminary experiments using this approach have also been encouraging (Pusuluri, 2020).…”
Section: Toward Online Applicabilitymentioning
confidence: 59%
See 1 more Smart Citation
“…Retraining an ANN on such a data set might strike a useful balance between the robustness of online training and the economy of offline training. Similar approaches have shown promise for comparable problems (Subel et al., 2021); our preliminary experiments using this approach have also been encouraging (Pusuluri, 2020).…”
Section: Toward Online Applicabilitymentioning
confidence: 59%
“…The example of data set enrichment presented here also offers encouragement to resolving instabilities that develop over several time steps. As it turned out to be overly optimistic to assume that an ANN trained on exact E F and E  combinations could handle erroneous E F in the early stages of a predictor-corrector scheme, it may also be too ambitious to expect that it will handle erroneous (Subel et al, 2021); our preliminary experiments using this approach have also been encouraging (Pusuluri, 2020).…”
Section: Toward Online Applicabilitymentioning
confidence: 95%
“…For example, Maulik et al [25,39] and Xie et al [40][41][42] have, respectively, developed local data-driven closures for 2D decaying homogeneous isotropic turbulence (2D-DHIT) and 3D incompressible and compressible turbulence using multilayer perceptron artificial neural networks (ANNs); also see [22,[43][44][45][46]. Zanna and Bolton [29,47], Beck and colleagues [26,48], Pawar et al [19], Guan et al [20], and Subel et al [49] developed non-local closures, e.g., using convolutional neural networks (CNNs), for ocean circulation, 3D-DHIT, 2D-DHIT, and forced 1D Burgers' turbulence, respectively. While finding outstanding results in a priori analyses, in many cases, these studies also reported instabilities in a posteriori analyses, requiring further modifications to the learnt closures for stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have shown that embedding physical insights or constraints can enhance the performance of data-driven models, e.g., in reduced-order models [e.g., [50][51][52][53][54][55][56][57] and in neural networks [e.g., 38,49,[58][59][60][61][62][63][64][65][66][67][68][69]. There are various ways to incorporate physics in neural networks (e.g., see the reviews by Kashinath et al [70], Balaji [71], and Karniadakis et al [72]).…”
Section: Introductionmentioning
confidence: 99%
“…Large-eddy simulation (LES) is an effective approach which adopts the coarse mesh to merely resolve the large flow scales and model the effect of residual subgrid scales (SGS) on the resolved large scales [4,5,6,7]. Extensive SGS models are proposed to reconstruct the unclosed SGS stress in previous works, including the Smagorinsky model [8,9,10], the velocity-gradient model (VGM) [11], the scale-similarity model [12,13], the implicit LES (ILES) [14,15,16], the Reynolds-stress-constrained LES model [17], the datadriven models [18,19,20,21,22,23,24,25], etc. The Smagorinsky model is one of the commonly-used SGS models whose model coefficient for the original version is statically adjusted by the experimental and DNS data in the early stage.…”
Section: Introductionmentioning
confidence: 99%